Role Of Magnesium In The Regulation Of Type 2 Diabetes (The Review of Diabetic Studies, 2025)
Magnesium is an important mineral very essential for glucose homeostasis and insulin sensitivity. Magnesium is involved in reactions like kinases, protein synthesis, oxidation and insulin secretion. Magnesium is an intracellular cation plays a role in physiological and biological process like regulating insulin action, insulin mediated glucose uptake. Hypomagnesemia leads to tyrosine kinase activity impairment in insulin receptor levels leads to defective insulin action, insulin resistance and oxidative stress in type 2 DM and further development of chronic condition like heart diseases, macrovascular defects like stroke, myocardial infarction and peripheral artery diseases, microvascular defects like nephropathy, neuropathy and retinopathy. The Homeostasis of magnesium is highly regulated by absorption in the intestine, storage of bone and renal excretion.  The observation of this review is serum magnesium levels strongly correlated to glycemic control and recommends monitoring serum magnesium levels in type 2 diabetes and supplementation should be considered in the management of diabetes.